Therapeutic Potential of Quercetin Derivatives: In Silico Investigation of HIV-1 Protease Inhibition - Aziz, Husna Abdul; Camin, Yeremiah Rubin; Prasasty, Vivitri Dewi (Journal of Tropical Biodiversity, 2024)
Human Immunodeficiency Virus (HIV) type 1 is the predominant strain known for its impact on the immune system and its propensity for mutation. According to the World Health Organization (WHO), the global infection count reached 37.9 million in 2018, with alarming rates of mortality and morbidity. Ongoing drug discovery endeavors encompass various facets, including investigations into HIV protease—a key enzyme in the cleavage process of gag and gag-pol polyprotein chains essential for the genesis of new virions. While numerous studies suggest the inhibitory potential of quercetin against HIV-1, comprehensive exploration regarding its interaction with the HIV-1 protease receptor remains limited. This study aimed to elucidate the therapeutic potential of quercetin derivative compounds as viable candidates for HIV protease inhibition. Employing in silico analysis, molecular docking of 36 quercetin derivative compounds with the HIV-1 protease receptor (code 3SO9) using the Pyrx-Autodock Vina-Open Babel platform was conducted. Prior to docking, ligand preparation was meticulously performed using Autodock Tools 1.5.6, with geometry optimization utilizing Avogadro software. The interaction was assessed through Gibbs free energy (∆G) scoring, where a more negative ∆G value indicated a stronger binding propensity between the ligand and receptor. The docking results revealed that 22 quercetin derivative compounds exhibited Gibbs energy (∆G) values lower than the original ligand, darunavir. However, 5 compounds deviated from Lipinski's rule, while 17 compounds adhered to Lipinski's criteria. Consequently, these 17 quercetin derivative compounds exhibit promising potential as candidate drugs for HIV-1 protease inhibition.